“Bloodless” Neurosurgery Among Jehovah's Witnesses: A Comparison with Matched Concurrent Controls - Hardesty, Douglas A.; Doerfler, Sean; Sandhu, Sukhmeet; Whitmore, Robert G.; Ford, Patricia; Rushton, Scott; LeRoux, Peter D. (World neurosurgery, 2017)
Jehovah's Witnesses (JW) are a Christian faith with >1 million members in the United States who do not accept autologous blood transfusions. The optimal management of these patients undergoing neurosurgical procedures is not well defined. Here, we examined the feasibility and safety of JW undergoing neurosurgery in a blood management program. Sixty-eight JW patients including 23 men and 45 women (mean age 53 ± 12 years) who underwent a variety of cranial (n = 19) and spinal (n = 49) neurosurgical procedures during a 5-year period were identified retrospectively and their hospital charts, anesthetic records, and operative reports reviewed. A concurrent cohort of sex-, age-, and procedure-matched non-JW controls also was identified. Among JW patients, a cell-saving system was used in 27 cases, with blood retransfused in 13 cases. Lactated Ringers solution was used extensively intraoperatively; albumin was given to 15 patients. The median decrease in hemoglobin was 2.1 g/dL. One patient had a postoperative hemoglobin value <7 g/dL. One patient returned to the operating room to revise a lumbar pedicle screw, and one patient had postoperative seizures. No cardiopulmonary complications, sepsis, pneumonia, or wound infection were observed. Compared with the matched control group, similar outcome results were observed. Blood loss and operative time also were similar in JW patients and controls. Neurosurgical procedures in Jehovah's Witnesses are feasible, safe, and have similar outcomes to patients willing to accept transfusion when managed within a multidisciplinary blood-management program.